GE_GERICHTE P/3173/2023 vom 7. Juli 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;VOIES DE FAIT;MENACE(DROIT PÉNAL);INJURE;COMMERCE DE STUPÉFIANTS;SÉJOUR ILLÉGAL;ENTRÉE ILLÉGALE;CONCOURS D'INFRACTIONS;CONTRAVENTION;EXPULSION(DROIT PÉNAL) | CP.126.al1; CP.180.al1; CP.177.al1; CP.286.al1; LStup.19.al1.letc; LStup.19.al1.letd; LEI.115.al1.leta; LEI.115.al1.letb; LEI.119.al1; CP.49; CP.66.alabis; CP.106